2016
DOI: 10.3389/fpsyg.2016.01744
|View full text |Cite
|
Sign up to set email alerts
|

Influences on and Measures of Unintentional Group Synchrony

Abstract: Many instances of large-scale coordination occur in real-life social situations without the explicit awareness of the individuals involved. While the majority of research to date has examined dyadic interactions – those between two individuals – during intentional or deliberate coordination, the present review surveys the handful of recent studies investigating behavioral and physiological synchrony across groups of more than two people when coordination was not an explicit goal. Both minimal (e.g., visual inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In addition, our findings revealed that interactions at the content space of collaboration could produce PS, even in the absence of the emotional or motivational regulation that takes place at the relational space. It should be noted that investigation of PS in team collaboration is still in its infancy and standard measures of PS are no yet developed (Ellamil et al, 2016). Thus, the current study is not conclusive and could be regarded as a preliminary attempt to unearth SSRL processes with PS.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…In addition, our findings revealed that interactions at the content space of collaboration could produce PS, even in the absence of the emotional or motivational regulation that takes place at the relational space. It should be noted that investigation of PS in team collaboration is still in its infancy and standard measures of PS are no yet developed (Ellamil et al, 2016). Thus, the current study is not conclusive and could be regarded as a preliminary attempt to unearth SSRL processes with PS.…”
Section: Resultsmentioning
confidence: 71%
“…Physiological synchrony (PS) refers to the relation between physiological responses of interacting individuals as they perform a collaborative task (Henning, Armstead, & Ferris, 2009). PS develops spontaneously and unintentionally, and thus, can be indexed by measuring responses of the autonomic nervous system (ANS) (Ellamil, Berson, & Margulies, 2016;Palumbo, Marraccini, Weyandt, Wilder-Smith, McGee, Liu, & Goodwin, 2016;Strang, Funke, Russell, Dukes, & Middendorf, 2014). Electrodermal activity (EDA) and heart rate (HR) activity are considered popular measures derived from the ANS.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Physiological synchrony (PS) is defined as the temporal alignment or correspondence in physiological activity between two or more interacting individuals (Ellamil et al, 2016;Helm et al, 2018;Palumbo et al, 2017). PS can happen unintentionally and automatically (Ellamil et al, 2016), and has been found in different species (Ham et al, 2023) as well as between species (Keeling et al, 2009). In humans, PS is linked to important components of social inter-actions, such as mimicry of gestures and facial expression, emotional contagion (i.e.…”
Section: Physiological Synchronymentioning
confidence: 99%
“…The co-occurrence and interdependence of changes in physiological reaction across interaction partners is called physiological synchronization [Ellamil et al (2016); Palumbo et al (2017), PS;], also referred to as empathic resonance or linkage. This cross-reactivity among group members or dyads has emerged as an important phenomenon to consider when investigating social processes.…”
Section: Introductionmentioning
confidence: 99%